2017
DOI: 10.1111/jcpp.12687
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Understudied populations within the autism spectrum – current trends and future directions in neuroimaging research

Abstract: Background Autism spectrum disorders (ASDs) are a heterogeneous group of neurodevelopmental conditions that vary in both etiology and phenotypic expression. Expressions of ASD characterized by a more severe phenotype, including autism with intellectual disability (ASD+ID), autism with a history of developmental regression (ASD+R), and minimally verbal autism (ASD+MV) are understudied generally, and especially in the domain of neuroimaging. However, neuroimaging methods are a potentially powerful tool for under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 119 publications
(171 reference statements)
3
92
0
1
Order By: Relevance
“…Further, both quantitative and qualitative sex differences have been detected in the neuroanatomy of children (Retico et al, 2016) and adults (Ecker et al, 2017) with ASD, and the brainstem is part of such sexually dimorphic brain regions (Lai et al, 2013). None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017). None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, both quantitative and qualitative sex differences have been detected in the neuroanatomy of children (Retico et al, 2016) and adults (Ecker et al, 2017) with ASD, and the brainstem is part of such sexually dimorphic brain regions (Lai et al, 2013). None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017). None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume. None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017). Moreover, the contribution of methodological variability to metrics of brainstem volume is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ASD research is unfortunately biased towards the sampling of highfunctioning individuals, likely under-representing subgroups with lower nonverbal intelligence ability. The proportion of cohorts with neuroimaging data available is even smaller (Jack & Pelphrey, 2017). Interpretations of findings are generally limited to sampled cohorts, and extension of assumptions to understudied ASD populations should be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In data-driven studies, such data can contribute to building multimodal classifiers, in combination with other data streams, that can be help identify subgroups within ASD. The practical challenges of running Commentary on Jack and Pelphrey (2017) neuroimaging experiments on low-functioning individuals with ASD have been highlighted by the authors of the review, alongwith evidence-backed suggestions for overcoming these challenges.…”
Section: Neuroimaging and Beyondmentioning
confidence: 99%